Anticancer effect of a pyrrole‐imidazole polyamide‐triphenylphosphonium conjugate selectively targeting a common mitochondrial DNA cancer risk variant in cervical cancer cells. Issue 5 (28th October 2022) - Yao, Jihang; Takenaga, Keizo; Koshikawa, Nobuko; Kida, Yuki; Lin, Jason; Watanabe, Takayoshi; Maru, Yoshiaki; Hippo, Yoshitaka; Yamamoto, Seigi; Zhu, Yuyan; Nagase, Hiroki
Abstract: Cervical cancer remains a major threat to women's health, especially in countries with limited medical resources, and new drugs are needed to improve patient survival and minimize adverse effects. Here, we examine the effects of a triphenylphosphonium (TPP)‐conjugated pyrrole‐imidazole polyamide (CCC‐h1005) targeting the common homoplasmic mitochondrial DNA (mtDNA) cancer risk variant (ATP6 8860A>G) on the survival of cervical cancer cell lines, cisplatin‐resistant HeLa cells and patient‐derived cervical clear cell carcinoma cells as models of cervical cancer treatment. We found that CCC‐h1005 induced death in these cells and suppressed the growth of xenografted HeLa tumors with no severe adverse effects. These results suggest that PIP‐TPP designed to target mtDNA cancer risk variants can be used to treat many cervical cancers harboring high copies of the target variant, providing a foundation for clinical trials of this class of molecules for treating cervical cancer and other types of cancers. Abstract : What's new? Recently, pyrrole‐imidazole polyamides, a class of cell‐permeable and programmable DNA minor groove binders, have shown potential in disrupting oncological targets in the genome. Here, the authors present the first report of a pyrrole‐imidazole polyamide‐triphenylphosphonium conjugate with the ability to target a common and preferentially homoplasmic cancer risk variant in mitochondrial DNA. The conjugate showed cervical cancer cell cytotoxicity and suppressed tumor growth with no severe adverse effects. This novel approach bypasses the absence of known mitochondrial DNA mutation hotspots and expands the potential clinical application of mitochondrial modulation for cancer treatment.